AB1163 Looking for minimum standards in care for children with localized scleroderma-result of the consensus meeting in hamburg germany on the 11th of december 2011. Part II. treatment of juvenile localised scleroderma. (23rd January 2014) - Foeldvari, I.; Constantin, T.; Höger, P.; Nemcova, D.; Pain, C.; Torok, K.; Weibel, L.; Clements, P.
Abstract : Background: Juvenile localised scleroderma (jlSc) is an orphan disease. There are currently no guidelines regarding diagnosis, follow up and treatment. Objectives: In the frame of the PRES scleroderma working group this consensus meeting was set up to gain consens regarding this issues. Methods: Members of the PRES scleroderma working group were invited to participate. Two pediatric dermatologist were invited. P. Clements was invited to moderate the meeting. A nominal group technique was used. 75% consensus was defined as agreement. Results: The group reached agreement on all discussed topic. Topical treatment is appropriate as therapy for small circumscribed superficial morphea lesions (plaque morphea) in non-cosmetically sensitive areas. Suggested topical treatment with best evidence: a.Tacrolimus 0.1% b, Vitamin D 0.005%; c. Topical steroids; d. Imiquimod Phototherapy is suggested for extending circumscribed superficial lesions, preferentially above the age of 12. UVA-1 is preferable; alternatively UVB narrowband can be used as an alternative. PUVA therapy should be avoided The group agreed that systemic treatment beyond topical treatment is suggested for active lesions in: a.linear scleroderma; b. Deep and pansclerotic morphea; c. Lesion in cosmetically sensitive areas; d. Lesions crossing joints; e. Generalized plaque morphea Consensus for first line systemic therapy among the group was unanimously agreed upon as methotrexate15 mg/m 2 /week, max 25 mg/week. a. Bridging therapy with glucocorticoids was suggested in this group, particularly in rapidly progressive and severe disease, such as lesions crossing the joints and cosmetically disfiguring disease. b. A glucocorticoid taper was suggested to be discontinued by 4 months (based on uveitis data). Physical and/or occupational therapy is recommended for any patient with decreased joint range of motion or muscle weakness. It was agreed that the aim of the treatment is to reach inactive disease If inactive disease is not reached after 6 months of systemic treatment or there is no improvement after 3 months of systemic treatment, it is recommended to switch systemic therapy There are currently no evidence based data to make suggestions in the case of methotrexate non-response, but there are possible options, such as mycophenolate mofetil, rituximab, tocolizumab …. Remission was defined by the group as 12 months of inactive disease on medication. The group agreed that after at least 12 months of inactive disease that systemic treatment can be stopped., based on case series. The group agreed to treat extracutaneous manifestations (ECM) associated with jLS according the treatment guidelines for the particular ECM (Uveitis, arthritis, seizures …). Conclusions: Topical treatment of small superficial circumscribed morphea lesions and systemic treatment with MTX +/- corticosteroids for all other subtypes of jLS was unanimously agreed upon. The duration of treatment and alternative therapies require more investigation. Disclosure of Interest: None Declared